Optimum wet treatment process for upgrading Andrassy and Mansuli bentonite and their applications in petroleum industry - Samsuri, Ariffin; Kien Ping, Leyong (2002)
Bentonite from two areas of Sabah, Andrassy and Mansuli had been proven as non-sodium based bentonite, which is different from standard bentonite used in petroleum industry. This study complies a wet treatment process to upgrade the low quality non-sodium based bentonite to sodium based variety.Several sodium sources have been studied but only the sodium carbonate can successfully be used to upgrade these bentonite. Other parameters that included in this study are bentonite to sodium carbonate solution ratio (moisture), sodium carbonate concentration, treatment time and pH. The results obtained after wet treatment indicate improvement of cation exchange capacity varying from 22% to 36% of the original CEC values. However, the upgraded bentonite failed to fulfil the API (American Petroleum Institute) requirements for rheological properties when used as material in drilling mud and oilwell cement. Thereafter, certain polymer extender had been added to improve rheological properties of the upgraded bentonite slurry so that it can be used as a drilling mud material and oilwell cement additive. Generally, the degree of bentonite quality improvement mainly depend on the origin of bentonite itself, it's composition, especially the percentage of momtmorillonite content in bentonite, chemical used in the treatment process and it's concentration and treatment time.